Unlocking Potential: The Transformative Power of Life Skills Education in Empowering Youth for Success - Haerani, Ira; Sari, Arni Safira Wanda (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study delves into the effects of life skills education on children's empowerment and success in various areas. Using a combination of research methods such as descriptive facts, paired-samples t-checks, regression analyses, ANCOVA, and Pearson correlational analyses, the study explores the impact of life skills interventions on enhancing important abilities in youth. The study reveals significant enhancements in people's perceived abilities, particularly in communication, decision-making, and problem-solving, after the intervention. Regression analyses demonstrate how life capabilities, particularly verbal communication, can predict academic achievement, career advancement, and personal growth. The ANCOVA results highlight the enduring influence of life skills training on academic performance. Correlational analyses by Pearson emphasize strong correlations between lifestyle skills and indicators of fulfillment. This analysis highlights the transformative power of life skills training in empowering young people for success in various aspects of life.